Learners' Perceptions on the Use of Oral Corrective Feedback in One-to-One EFL Classroom - Sitti Syakira; Sahril Nur (Makassar State University, 2022)
Abstract. Learners’ perception plays an important role in evaluating the teaching and learning process and has an impact to the teacher’s performance during the teaching and learning process. Applying descriptive qualitative method with case study design, this study highlighted the learners’ perceptions and their preference of oral corrective feedback utilized by the teachers during the teaching and learning process. By using purposive sampling, this research involved one teacher and two learners as research participants at an English course called Amsterdam Institute located in Makassar. The data, collected through semi-structured interview and observation, resulted that the learners found themselves facilitated in responding the teacher’s utterances since the teacher’s oral corrective feedback were helpful to lead the learners’ accuracy or just to help them acknowledge their errors in terms of grammar, lexis, the use of L1, and particularly in phonology (pronunciation). Furthermore, inconsistencies between the students’ preference and the teacher’s feedback use in terms of the time to provide oral corrective feedback are identified. Students preferred being given time to work out their error, while teacher mostly gave feedback directly. Thus, it can be concluded that giving more time for students to provide self-repair can be a way for students to make sense of error they committed. The results further highlight a significant impact for teachers’ beliefs on their corrective feedback practices, especially for those teaching using a tailor-made system. Finally, the implication of this study is discussed.Keywords: Learners’ Perceptions, Oral Corrective Feedbacks, One-To-One EFL Classroom.